EFFECTIVENESS OF SCHOOL CARE IN THE MANAGEMENT OF SCHOOL UNHEALTHY FOOD CENTRES LIVING IN SCHOOL - Ester Ria Nainggolan (Adisam Publisher, 2025)
School nurses play a crucial role in the management of School Health Units (UKS) in boarding schools, which aim to ensure the overall health and well-being of students. This study evaluates the effectiveness of school nurses in UKS management through the various tasks they perform, such as routine health checks, health education, and mental health support. The results showed that nurses were able to detect health problems early, provide education that increased students' awareness of the importance of maintaining good health, and provide mental support that encouraged stress management. The contribution of nurses in creating a healthy and supportive school environment is essential to ensure that students can learn and develop optimally. This conclusion emphasises the importance of the role of nurses in boarding school UKS and suggests increased institutional support to strengthen their function.